Bronchogenic cyst of gastric cardia - case report and literature review - Erbenová, A; Placrová, B; Špůrková, Z; Horák, P (Rozhledy v chirurgii, 2021)
INTRODUCTION: Intramural bronchogenic cysts of the esophagus are very rare. They are mostly found in the upper mediastinum. Symptoms are caused by compression of surrounding structures by the cyst or complications of the cyst. However, the majority are asymptomatic. CASE REPORT: We describe the case of a 30-year-old female patient who underwent surgery at our institution for a tumor of the gastric cardia protruding intraluminally. The tumor was found incidentally during upper endoscopy before a planned bariatric surgery. A solid lesion originating from the muscle layer of the cardia wall was described based on endoscopic ultrasound. A CT scan did not show any infiltration of surrounding structures or disease dissemination. We performed laparoscopic enucleation of the tumor combined with partial fundoplication to close the defect in the muscular layer of the esophagus. Histopathology report surprisingly confirmed a bronchogenic cyst in the gastric cardia wall. The patient healed primarily and was soon discharged without complications. Two months later she underwent sleeve gastrectomy for obesity. Seven months following the bronchogenic cyst enucleation an endoscopic balloon dilation was performed on the patient with good effect upon diagnosing a relative gastric cardia stenosis. CONCLUSION: The diagnosis of esophageal bronchogenic cysts is usually difficult. Histopathology results are crucial to determine the definitive diagnosis. Endoscopy and imaging techniques, including endoscopic ultrasound, play an important role in the diagnostic process. Most authors prefer complete removal of the cyst, endoscopic or surgical, due to possible cyst complications, diagnostic uncertainty, and certainly in symptomatic patients. The complication rate is minimal.
Keywords: dospělí; Humans; bronchogenní cysta; Esophageal Cyst; benign gastric cardia tumor; kardie; Endosonography; Adult; bronchogenic cyst; jícnová cysta; mediastinum; Mediastinum; endosonografie; Bronchogenic Cyst; ženské pohlaví; Cardia; laparoscopic enucleation; lidé; Female